Pre-operatory care from the surgical client perspective - Callegaro, Giovana Dorneles; Baggio, Maria Aparecida; Nascimento, Keyla Cristiana do; Erdmann, Alacoque Lorenzini (Rev Rene, 2010)
The objective of this qualitative study was to better understand how the surgical patient perceives the pre-operatory care offered by nursing and health care professionals. Twenty-three subjects in a surgical room of a public hospital in Santa Catarina, Brazil were interviewed. Four categories emerged from data content analysis: Living care and non-care in the surgical experience; Identifying surgical room professionals; Experiencing surgical delays/postponements/cancellations; and Perceiving pre-operatory orientations. Communication, dialogue, information, respect, and pre-operatory orientation found the care relationship between the care-giver and the person receiving care; The little importance given by professionals to its identifi cation, the lack of pre-operatory orientation, and late, postponed, and cancelled surgeries not communicated in time weaken this relationship. It is up to nursing and health care professionals to critically refl ect upon these results, seeking to attend to the multi-dimensionality of the being receiving pre-operatory care.